Assessment of temperament and its effect on weaning performance for Aubrac and Charolais weaned calves - Szentléleki, Andrea; Domokos, Zoltán; Blottura, Claudio; Alberti, Massimiliano; Tőzsér, János (Acta Agraria Debreceniensis, 2009)
The purposes of the present study are to compare the temperament of calves of different breed and sex at weaning, to analyse the effect of temperament on weaning performance, and to define the correlations between the previous traits. In the experiment carried out in Gelej in 2006 the behaviour of 61 Aubrac and 25 Charolais calves (39 heifer and 47 bull calves) was assessed at weaning. The weight (WW) and the age of animals were detected, in addition temperament (TEMP) of them was scored. The weaning age (AU: 190±16.96 days, CH: 176±14.94 days; P<0.001) and the weaning weight adjusted to 205 days of age (CWW) (AU: 192.39±31.32 kg, CH: 213.80±23.99 kg; P<0.01) of the two breeds significantly differed of each other. The temperament of calves was evaluated by scale test on a 5-point scale during weighing. The data were processed by SPSS 14.0 program package (Mann-Whitney U test, MANOVA, Tukey test, Spearman rank correlation test). Significant difference was revealed between the two breeds in TEMP (AU: 2 scores and CH: 3 scores; P<0.001), furthermore also difference was proven between the bull calves of Aubrac and Charolais in the behaviour (AU: 2 scores and CH: 3 scores, P<0.01). Analysing the effect of sex both for 86 calves and each breed, it was showed that the TEMP of the heifer and bull calves was equalled (P>0.10). Both of the WW and CWW were influenced by the behaviour of calves (P<0.05), which meant that the more excitable calves had higher WW and CWW. Positive, weak correlation coefficients were calculated among the TEMP, the WW and the CWW (rrank=0.28 and rrank=0.31; P<0.01). By their results it was concluded that in young age not only the performance but also the behaviour of calves are determined by the calf rearing ability of suckling cow.